Experimental validation of VOR (VHF Omni Range) navigation system for stratospheric flight - Marzioli P.; Frezza L.; Curiano F.; Pellegrino A.; Gianfermo A.; Angeletti F.; Arena L.; Cardona T.; Valdatta M.; Santoni F.; Piergentili F. (Acta Astronautica, 2021)
This paper presents the results of STRATONAV experiment to test the precision of the VOR (VHF Omni Range) aircraft navigation system in stratosphere. The experiment has been conducted by the S5Lab research group at Sapienza University of Rome in the framework of the REXUS/BEXUS Programme. STRATONAV has been successfully launched on-board the BEXUS 22 stratospheric balloon from Esrange Space Center in Kiruna, Sweden, in 2016. The main payload was composed by two typologies of VOR receivers, a commercial portable receiver and a Software Defined Radio (SDR), alongside the bus and positioning, attitude and temperature sensors. STRATONAV succeeded in collecting VOR radials for the whole duration of the balloon flight. The results prove that VOR can be used as back-up navigation system for stratospheric platforms, ensuring a reliability improvement, while being applied to smaller payloads as primary system for a cost and complexity reduction of experiment developments. The paper analyzes the collected VOR data during the balloon flight. Accuracy and performance plots with respect to distance from the VOR stations and altitude are presented and discussed. The mean errors and standard deviations from all stations for both the receivers are shown with an analysis over the recorded errors. Finally, future perspectives, analyses and applicability of the research are exposed.